Experimental study on crack resistance of typical steel-bridge-deck paving materials. (29th March 2021) - Fan, Xiangyang; Luo, Rong
Highlights: Crack resistance performance of three steel-bridge-deck paving materials are determined using an improved overlay test. Theoretical equations are formulated to calculate crack resistance performance based on an improved overlay test. Impact of temperature is investigated by comparing the determined fracture properties. Abstract: In this study, the crack resistance performance of three steel-bridge-deck paving materials (epoxy asphalt mixture EA-10, Gussasphalt mixture GA-10, and high-elastic SMA-10 asphalt mixture) are tested using an improved overlay test (OT test). First, it is necessary to conduct a theoretical analysis. The test is conducted in two phases: non-destructive and destructive stages. In the non-destructive stage, the relationship between loading the cycle-strain integral area and the strain-integral, area-different crack lengths are established. In the OT test, the loading pattern is performed in a half-sine wave pattern. In the destructive stage, the relationship between the peak load and the strain integral area is established. Moreover, a virtual displacement work model is developed. Second, through non-destructive and destructive tests, a continuous model of the paving material's non-destructive test parameters E 1 and m is developed. In addition, based on the results of the theoretical analysis, the expressions of the anti-cracking performance parameters A and n of different paving materials at different temperatures are presented. Depending on the relationship between the loading cycle and the crack length, the crack performance parameters A and n of different paving materials at different temperatures are calculated. Based on the test results, it is evident that at the same temperature, the crack resistance parameters n of GA-10 and EA-10 are comparable and significantly smaller than that of SMA-10, indicating that GA-10 and EA-10 have better crack resistance than SMA-10. It is also evident that a change in temperature results in a slight variation in A and n for GA-10 and EA-10, indicating a minute temperature sensitivity of the crack resistance of GA-10 and EA-10; thus, GA-10 and EA-10 are more suitable for large temperature variation applications.